Hypothermia-Associated Coagulopathy: A Comparison of Viscoelastic Monitoring, Platelet Function, and Real Time Live Confocal Microscopy at Low Blood Temperatures, an in vitro Experimental Study - Wallner, Bernd; Schenk, Bettina; Hermann, Martin; Paal, Peter; Falk, Markus; Strapazzon, Giacomo; Martini, Wenjun Z.; Brugger, Hermann; Fries, Dietmar (Frontiers in Physiology, 2020)
Hypothermia has notable effects on platelets, platelet function, fibrinogen and coagulation factors. Common laboratory techniques cannot identify those effects, because blood samples are usually warmed to 37°C before analysis and do not fully reflect the in vivo situation. Multiple aspects of the pathophysiological changes in humoral and cellular coagulation remain obscure. This in vitro experimental study aimed to compare the measurements of thromboelastometry (TEM), multiple-electrode aggregometry (MEA) and Real Time Live Confocal Imaging for the purpose of identifying and characterizing hypothermia-associated coagulopathy. Blood samples were drawn from 18 healthy volunteers and incubated for 30 minutes before being analyzed at the target temperatures (37°C, 32°C, 24°C, 18°C, and 13.7°C). At each temperature thromboelastometry and multiple-electrode aggregometry were measured. Real Time Live Confocal Imaging was performed at 4°C, 24°C and 37°C. The images obtained by Real Time Live Confocal Imaging were compared with the functional results of thromboelastometry and multiple-electrode aggregometry. Thromboelastometry standard parameters were impaired at temperatures below baseline 37°C (ANOVA overall effect, p<0.001): clotting time was prolonged by 27% at 13.7°C and by 60% at 18°C (p<0.044); clot formation time was prolonged by 157% (p<0.001). A reduction in platelet function with decreasing temperatures was observed (p<0.001); the area under the curve at 13.7°C was reduced by 96% (ADP test), 92% (ASPI test) and 91% (TRAP test) of the baseline values. Temperature-associated changes in coagulation were visualized with Real Time Live Confocal Imaging. Molecular changes such as the temperature-associated decrease in the fibrin network are paralleled by cellular effects like the lesser activity of the platelets as a result of decreased temperature. The maximum clot firmness (MCF) in TEM only changed slightly within the temperature range tested. The inhibitory effects of temperature on clot formation were visualized with Real Time Live Confocal Microscopy and compared with standard point-of-care testing. Inhibition of clotting factors and impaired platelet function are probably a result of hypothermia-induced impairment of thrombin. Measurement of MCF in TEM does not fully concur with Real Time Live Confocal Microscopy or MEA in hypothermia.